Perioperative Management of a Patient with Secreting Paraganglioma Undergoing Cesarean Section - Ana Rita Bettencourt; Catarina Alves (Case Reports in Anesthesiology)
Paraganglioma is a catecholamine-secreting tumor (CST) in extra-adrenal autonomic ganglia and a rare cause of hypertension during pregnancy. If not properly treated, it can lead to disastrous outcomes for both the mother and fetus. This report describes the successful anesthetic management of a paraganglioma diagnosed during pregnancy. A pregnant woman, with 32 weeks of gestational age, presented with severe paroxysmal hypertension, refractory to methyldopa and nifedipine at maximum dosages, headache, sweating, and palpitations. Diagnostic work-up was positive for elevated serum and urinary normetanephrines, and magnetic resonance showed a solid nodule above the hilum of the right kidney, suggestive of paraganglioma. Optimal alpha-blockade was achieved with doxazosin, and given the advanced gestational age, tumor resection was postponed until after delivery. Cesarean delivery was scheduled at 34 weeks, under combined spinal-epidural anesthesia and continuous blood pressure monitoring. Antihypertensive drugs were prepared for immediate administration as needed. Intraoperative and postoperative periods went uneventfully for both the mother and newborn, both under intensive care observation for 24 h.